(3eLGR GdbQBfs - (3YR GdOjf YHO GdYRjR Hf YHO GdSdGe Hf CHh GdbGSe Hf GdMSf GdSdej GdOeTbj, GdYR Hf YHO GdSdGe,J (B660 (3g` s
(3ChdgG (B:s
(3acd cdeI jSjQI LeYJ cKjQI efgf ef LhGeY Gdcde s
(3BNQgG (B:s
(3agPG eG JjSQ PcQg ef CfhGY GdMPa hGdeLGR s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B21s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1590s
(3eUOQ GbJfGA GdCUd (B:s
(3GdRGhjI GdMeRGhjI (B- (3GdeZQH (B(74) s
Keywords: (3GdHdGZIs